Uji aktivitas antiglikemik ekstrak kulit labu kuning (Cucurbita moschata) secara in vitro - Auliyah, Mayasin Tania; Toemon, Angeline Novia; Martani, Natalia Sri (Barigas: Jurnal Riset Mahasiswa, 2023)
Diabetes Mellitus is a chronic disease with the main symptoms of hyperglycemia. Phytochemical screening of pumpkin skin (Cucurbita moschata) contains alkaloids, flavonoids, saponins, steroids, terpenoids, and tannins which have potential as antiglycemic agents. This study aims to prove the antiglycemic activity of pumpkin peel extract (Cucurbita moschata) which acts as a reducing sugar and binds glucose in vitro using the Nelson Somogyi method. The sample of this study was pumpkin peel extract with concentrations of 60, 80, 100, 120, 140 ppm and 5 ppm quercetin as positive control. Pumpkin peel extract (Cucurbita moschata) has a potention as reducing sugar. The absorbance of each concentration of group 60, 80, 100, 120, 140 ppm is 0.400; 1.100; 1.182; 1.217; 1.505. The statistical test resulted p = 0.039, means the concentration of pumpkin peel extract (Cucurbita moschata) has an effect on decreasing glucose levels and resulted in EC50 = 56.1